Policy of WorldFish on Intellectual Property - WorldFish (CGIAR System Organization, 2016)
Intellectual assets (IA) are any results or products of research and development activities of any nature whatsoever (including but not limited to, knowledge, publications and other information products, databases, improved germplasm, technologies, inventions, know-how, processes, software, and distinctive signs), whether or not they are protected by IP Rights.